SARS-CoV-2 vaccination, booster, and infection in pregnant population enhances passive immunity in neonates - Elisabeth A. Murphy; Camila Guzman-Cardozo; Ashley C. Sukhu; Debby J. Parks; Malavika Prabhu; Iman Mohammed; Magdalena Jurkiewicz; Thomas J. Ketas; Sunidhi Singh; Marie Canis; Eva Bednarski; Alexis Hollingsworth; et al. (Nature Communications, 2023)
Abstract The effects of heterogeneous infection, vaccination and boosting histories prior to and during pregnancy have not been extensively studied and are likely important for protection of neonates. We measure levels of spike binding antibodies in 4600 patients and their neonates with different vaccination statuses, with and without history of SARS-CoV-2 infection. We investigate neutralizing antibody activity against different SARS-CoV-2 variant pseudotypes in a subset of 259 patients and determined correlation between IgG levels and variant neutralizing activity. We further study the ability of maternal antibody and neutralizing measurements to predict neutralizing antibody activity in the umbilical cord blood of neonates. In this work, we show SARS-CoV-2 vaccination and boosting, especially in the setting of previous infection, leads to significant increases in antibody levels and neutralizing activity even against the recent omicron BA.1 and BA.5 variants in both pregnant patients and their neonates.